Evaluation of the association between salivary biomarkers and oral health conditions: a cross-sectional study in a community setting - Dr. Rida Kainat, Om Pirkash, Rohan raja, Omesh Kumar, Vandana Dhanani, Sarwan Kumar, Muhammad Abubakar Abdullah, Khurram Shahzad (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Salivary biomarkers have emerged as potential indicators of oral health conditions due to their non-invasive and convenient nature. This study aims to evaluate the association between salivary biomarkers and oral health conditions in a community setting.Aim: The primary aim of this cross-sectional study is to investigate the relationship between salivary biomarkers and various oral health conditions, including periodontal disease, dental caries, and oral inflammation. By examining these associations, we seek to identify potential biomarkers that could aid in the early detection and monitoring of oral health conditions.Methods: A diverse community-based sample of participants aged 18 to 65 years will be recruited for this study. Salivary samples will be collected and analyzed for the presence of specific biomarkers related to inflammation, microbial activity, and tissue destruction. Additionally, participants' oral health conditions will be assessed through clinical examinations, including periodontal probing, caries index, and evaluation of oral inflammation. Statistical analysis, including regression models and correlation tests, will be employed to determine the associations between salivary biomarkers and oral health conditions.Results: The study findings will provide insights into the potential associations between specific salivary biomarkers and various oral health conditions. The results will be presented in a comprehensive manner, highlighting significant correlations, if any, between biomarker levels and the presence or severity of oral health conditions in the community sample.Conclusion: This cross-sectional study will contribute valuable information regarding the association between salivary biomarkers and oral health conditions in a community setting. The identified biomarkers may hold promise as non-invasive tools for early detection, monitoring, and risk assessment of oral health conditions, leading to improved preventive strategies and better oral healthcare outcomes